A Comparison of the Business Environments in U.S. and Japan - Němcová, Barbora (2018)
When comparing the business environments between the U.S. and Japan, several differences and similarities have been identified. The countries unsurprisingly differ geographically as well demographically, which is explained within the first chapter. After comparing economic factors, both countries display comparable attributes in various economic situations. Political aspects are similar such that a stable political environment is mirrored between the two, even though the more particular details, such as the government structure, are not the same. This is the same case in terms of the technological environment. The business culture is what predominantly sets the countries apart. From negotiation techniques to formal greetings; it is of vital importance that customs are appreciated in order for business to run smoothly when dealing with each country respectively.